Low‐cycle fatigue behaviour of ductile closed‐cell aluminium alloy foams. Issue 4 (17th October 2016) - Linul, E.; Şerban, D. A.; Marsavina, L.; Kovacik, J.
Abstract: This work investigates the fatigue response of a class of ductile closed‐cell aluminium alloy foams, known by their commercial name Alulight M8. In order to determine the yield stress of the used foams, preliminary experimental tests were performed, at room temperature, in monotonic compression on cylindrical specimens of 25 mm diameter and 25 mm height, with a loading speed of 10 mm/min. Fatigue tests were performed in uniaxial compression on cylindrical specimens (25 mm × 25 mm) with a stress ratio of R = 0.1, at a frequency of 10 Hz. The peak stress was varied from 110 to 135% of the yield stress in compression. Tested specimens were cut from the same cylindrical bar, and the density of the investigated material was 500 kg/m 3 ± 10%, or a total of 18 specimens being investigated. With the gathered experimental data, S–N curve was generated, and the effect of cellular structure (e.g. structure irregularity–the number and the size of cells) being investigated and discussed.